Clinical statistics analysis on the characteristics of pneumoconiosis of Chinese miner population - Wang, Mei-Fang; Li, Run-Ze; Li, Ying; Cheng, Xue-Qin; Yang, Jun; Chen, Wen; Fan, Xing-Xing; Pan, Hu-Dan; Yao, Xiao-Jun; Ren, Tao; Qian, Xin; Liu, Liang; et al. (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Background: Pneumoconiosis is one of the most common occupational diseases, which shows the progressive and irreversible pathological changes. It ultimately can induce pulmonary failure and lead to death. To date, these patients have no curative treatment option under the current standard of care, so it is especially important to delay the onset of the disease and slow down its progression. Therefore, understanding of clinical features of pneumoconiosis is particularly critical for medical intervention. Methods: We collected the clinical data from 118 pneumoconiosis cases of miners admitted in hospital and processed the statistics analysis by using the Chi-square test and the risk assessment. Results: Compared to other types of miners, gold miners are liable to cause Broncho-pulmonary co-infection with Chi-square value 18.748 and the P value